Feasibility of E-Magazine Media Submaterial Fungi Diversity Inventory Results in the Padang Tikar Protected Forest, Kubu Raya Regency - Ariswandi, Ariswandi; Yeni, Laili Fitri; Fajri, Hayatul (UNIB Press, 2025)
Learning media aims to improve the quality of teaching and learning and motivate students through engaging presentations. This study aimed to determine the feasibility of e-magazine media from the macroscopic fungi inventory in Padang Tikar Protection Forest, Kubu Raya Regency. The development of e-magazine media was carried out to become an additional information source on the fungi diversity submaterial. This study used a qualitative descriptive method of 2-stage research, including interviews and media making. The media-making stage was then divided into pre-production, production, and post-production. Media feasibility validation was carried out at the post-production stage with a Likert scale assessment and analyzed using Lawshe's formula. The media validation results obtained a CVI value of 1.00. The validation results exceeded the value of 0.99 criteria from 5 validators; it can be concluded that the e-magazine media is valid for use in the fungi diversity submaterial.